Agents and Peer-to-Peer Computing - Joseph, Sam (Springer, 2017)
This book constitutes the thoroughly refereed post-workshop proceedings of the 5th International Workshop on Agents and Peer-to-Peer Computing, AP2PC 2006, held in Hakodate, Japan, in May 2006, in the context of the 5th International Joint Conference on Autonomous Agents and Multi-Agent Systems, AAMAS 2006.